BCF implementation on FPGA - Adli Rizqulloh, Muhammad
At this time electronic information technology is in various fields in everyday life. One algorithm that has been developed by researchers in Indonesia is the BCF algorithm. The application of BCF algorithm in embedded systems is constrained by a low clock so that the encryption or decryption process of large data requires a long time. So we need a BCF engine that is embedded in embedded systems to speed up the encryption or decryption process. In this study, the design and implementation of the BCF engine in FPGA DE2 were carried out. Operations on the BCF engine are controlled by the Nios II processor as the host-processor. The test results show that this BCF engine can do 2847 times faster computing than just using the Nios II / e processor as an embedded system.